Analisis Komparasi Pengaruh CKPN dan Profitabilitas Terhadap Permodalan Bank yang Diukur Melalui Rasio Car Sebelum dan Sesudah Adaptasi PSAK 71 (Studi Kasus pada Bank Umum Buku 2 Yang Teregistrasi di OJK) - Farhan Zaki; Sudrajat Sudrajat (Pusat Riset dan Inovasi Nasional, 2024)
Competition between commercial banks is increasingly rapid and complex, causing changes in regulations that are binding on commercial banks. One of the regulatory changes is the application of PSAK 71 which replaces PSAK 55 concerning Financial Instruments. A previous study conducted by Suroso in 2017 simulated the impact of implementing PSAK 71 on bank performance as measured by the capital ratio, namely the Capital Adequacy Ratio. The results of this study stated that there was a decrease in the CAR ratio due to an increase in CKPN which was caused by a change in the CKPN calculation method. This research will measure the comparative influence of CKPN, ROA, and Size as control variables on the CAR ratio at BUKU